PHYSICAL THERAPY OF CHILDREN OF YOUNGER SCHOOL AGE WITH MENTAL RETARDATION - Nahorna, O. B. (Rehabilitation and Recreation, 2023)
Solving today’s challenges in the educational space presupposes the need to solve socio-pedagogical tasks. One of them is the provision of complex correctional assistance to children with mental retardation in both special and general educational institutions. The implementation of the system of inclusive education exacerbates this problem and becomes especially relevant. To date, the practical implementation of a complex program of physical therapy for children with mental disabilities in the process of learning in special and general educational institutions in any form of education – individual, integrated or in an inclusive class – remains unresolved. The purpose of the study is to analyze the tasks of the physical rehabilitation/therapy program for children with mental retardation of primary school age. Research methods – theoretical analysis, synthesis, generalization of scientific and methodological literary sources on the topic of research. Research results. The article examines the issues of complex rehabilitation influence during the educational process with children with mental retardation; general and specific disorders of the motor sphere of children of this category were analyzed; emphasis is placed on the need for systematic implementation of physical rehabilitation/therapy to improve the personal development of children with intellectual disabilities. In particular, it is worth noting that for the harmonious personal development of children with intellectual disabilities and ensuring a long-term and continuous corrective effect, the priority task of specialists is close cooperation with the children’s parents. Conclusions. Enough scientific and methodical works in the field of medicine, education, and physical therapy are devoted to the problem of rehabilitation of children with mental retardation; educational programs for obtaining educational services have been developed and systematized. However, the conditions for ensuring a systematic therapeutic effect by means of physical rehabilitation/therapy of children with limited intellectual abilities during their education in various forms of education in the elementary school have not been sufficiently worked out. The tasks of the physical rehabilitation/therapy program for children of this category include the formation of self-care skills in them; prevention of respiratory and somatic diseases, secondary disorders of the development of the musculoskeletal system, motor functions; formation of pupils’ motivation for a healthy lifestyle, for independent classes in physical education and sports; improvement of the social and household behavior model of children with special needs. In this regard, changes are needed in the professional training of future teachers of special and general educational institutions, physical education teachers, and primary school teachers, in order to be ready to provide a comprehensive rehabilitative impact on children with intellectual disabilities.